Investments in stock of banks implementing high social responsibility standards listed on the Warsaw Stock Exchange - Buszko, Michał (Copernican Journal of Finance & Accounting, 2014)
The paper characterizes benefits and evaluates profitability of investments in stock of banks participating in RESPECT Index, i.e. a special index distinguishing companies that implement high standards of corporate social responsibility. In the paper, there is a brief characteristics of RESPECT Index, its nature, goals and ways of functioning. After that, there are presented base statistics of investors’ return and risk related to the RESPECT Index. In the next part the author describes banks listed on WSE in Poland and their role in RESPECT Index. Further, there are included rates of return from investments in socially responsible banks versus WIG Banking index. The last part of the paper is related to analysis of the bank stock prices around the day of their entrance to RESPECT Index and their cumulative returns since listing within the Index on WSE.